Eusébio de Cesareia e a construção de uma identidade cristã através do diálogo com judeus, helenos e hereges sob a dominação romana - Sleder, Daniel (2019)
In this work we will try to understand how Eusebius of Caesarea, in writing Ecclesiastical History, reveals and at the same time builds a Christian identity, among the many possible and existing; as a Christian bishop and member of a provincial elite who lived between 260/265 and 339 AD, a period marked by the tension between transformations and permanence that was Late Antiquity in an environment of intense cultural dialogue between Jews, Christians and Helens, under Roman domination, incorporates, resigns and negotiates elements to form a Christian identity ideal, an elite ideal, based on the values of the Greco-Roman elite.